ORIENTATED FePt NANOCRYSTALS DEPOSITED ON POROUS SILICON - A. Khajehnezhad; R.S. Dariani; M. Farle; M. Akhavan (European Scientific Journal, ESJ, 2013)
FePt nanocrystals with L10 chemical order have high magnetic anisotropy. To form the hard magnetic L10 phase as prepared fcc FePt nanocrystals need to be heated to 600°C. We demonstrate that the morphology of chemically etched porous silicon (PS) substrates and the presence of a magnetic field during the annealing process (600 °C, 1 h) affect the particle arrangement and orientation. X-ray diffraction (XRD) and field emission scanning electron microscopy (FE-SEM) show the presence of the L10 ordered FePt particles (average diameter 15 nm) uniformly distributed on the substrate. The presence of perpendicular magnetic field during annealing increases the order parameter degree of L10 FePt NPs. These effects can be investigated from variations of the XRD peaks intensity ratio. Presence of magnetic field of 20mT in the perpendicular direction to the substrate surface increases the (001) peak intensity ratio with respect to (111) peak from 0.27 to 0.58. This effect is due to the superlattice formation at (001) direction.